Trust in Religious Leaders and Voluntary Compliance: Lessons from Social Distancing during COVID‐19 in Central Asia. Issue 3 (15th September 2022) - Jones, Pauline; Menon, Anil
Abstract: What is the relationship between trust in religious leaders and compliance with policies that are costly to the individual? Religious leaders often have the moral authority to affect individuals' willingness to adopt prosocial behaviors. Yet, that influence can be either positive or negative because religious leaders face mixed incentives to encourage compliance and their leadership is often decentralized. We argue that greater trust in religious leaders will increase compliance in countries with a dominant religion and centralized religious authority because religious leaders will offer a coherent message that aligns with state directives. We test our hypotheses using data from surveys fielded in Kazakhstan and Kyrgyzstan during the COVID‐19 pandemic. We find a positive and significant relationship between trust and voluntary compliance only in Kazakhstan, where religious leaders reduced the costs of compliance by enabling adherents to practice their faith while social distancing. We thus identify an alternative mechanism whereby trust promotes compliance.